Deleuze and American Literature - Bourassa, A. author. aut Link
IX, 210 p.
Keywords: Bourassa demonstrates what happens when the set of concepts developed by Deleuze come into contact with the complex and philosophically problematic worlds of William Faulkner, Cormac McCarthy, Edith Wharton and Ralph Ellison.